Magnetic system of thermonuclear reactor "Elemag" - Lavrent'ev, O.A.; Maslov, V.A.; Germanova, S.V.; Nozdrachov, M.G.; Oboznyj, V.P.; Shevchuk, B.A. (Вопросы атомной науки и техники, 2005)
The conceptual project of thermonuclear reactor "Elemag" is developed. The multislit electromagnetic trap with axisymmetric magnetic field geometry is assumed as a basis of the project. It is most simple and most investigated thermonuclear system. The description of reactor magnetic system, accounts of magnetic fields, ponderomotive forces, electrotechnical accounts of magnetic field coils are given in this paper.